Human NK Cell Activation Upon Stimulation With Interleukins - Lusty, Evan (My University, 2016)
The WHO predicts that by the year 2035 the world will be facing a “cancer tidal wave”. This has spurred on the development of many cancer immunotherapies. The adoptive transfer of ex vivo expanded NK cells is one such therapy that could have high efficacy and target specificity. However, the adoptive transfer of NK cells has some negative side effects. Fortunately, these are not due to the direct effects of the NK cells. Instead, toxicity arises from the systemic administration of IL-2 which supports NK cell function. To sidestep the need for IL-2 injections our project investigated the effect of stimulating NK cells with interleukin 12, 15, and 18 in vitro. Our hope is that one-day pre-stimulation of NK cells with these cytokines in vitro before their adoptive transfer will maintain NK cell activation and survival in vivo. Our research has revealed that ex vivo expanded NK cells stimulated with IL-12 and IL-18 +/- IL-15 significantly upregulates the expression of IFN-γ, TNF-α, CXCL-8, CCL3L1, and LTA. Furthermore, production of these cytokines can continue up to 72 hours post stimulation in vitro. If the production of these cytokines continues after adoptive transfer of NK cells into cancer patients it could drastically alter the anti-inflammatory milieu of the cancer patient. Our attention was then turned to elucidating the factors responsible for the long term activation of the NK cells in the IL-12 and IL-18 +/- IL-15 conditions. We have determined that the increase in production of proinflammatory cytokines is due to direct increases in IFN-γ transcription. The results of these trials will direct the future use of NK cells in clinical trials. Specifically, there is great potential for this research to be used to predict potential negative side effects of using ex vivo expanded and stimulated NK cells as a cancer immunotherapy.
Keywords: Immunology, NK cells, Cytokines, Interleukins